Comparative analysis of load/deflection ratios of conventional and heat-activated rectangular NiTi wires - Fabio Schemann-Miguel; Flávio Cotrim-Ferreira; Alessandra Motta Streva; Alexander Viégas de Oliveira Aguiar Chaves; Andréia Cotrim-Ferreira (Dental Press Editora, 2012)
OBJECTIVE: This study compared the load-deflection ratios between 0.019 x 0.025-in rectangular orthodontic wires using 5 conventional preformed nickel-titanium (NiTi) and 5 heat-activated NiTi archwires from four different manufacturers (Abzil, Morelli, 3M Unitek and Ormco), totaling 40 archwires. The archwires were placed in typodonts without tooth # 11 and tested using a universal testing machine connected to a computer. RESULTS: The comparisons of mean load-deflection values of conventional NiTi wires revealed that the lowest mean-deflection ratio was found for 3M Unitek, followed by Ormco, Morelli and Abzil. Regarding the heat-activated wires, the lowest load-deflection ratio was found for Ormco, followed by 3M Unitek, Abzil, and Morelli. CONCLUSION: The comparison of mean load-deflection ratios revealed that the heat-activated wires had lowest mean load-deflection ratios, and this trend was seen during all the study. However, at 2-mm deflection, mean load-deflection ratios for heat-activated Morelli and conventional 3M Unitek wires were very similar, and this difference was not statistically significant.